Modified Baer-Nunziato Model for the Simulation of Interfaces Between Compressible Fluids (Communications in Computational Physics, 2011)
In this paper we proposed a modified Baer-Nunziato model for compressiblemulti-fluid flows, with main attention on the energy exchange between the twofluids. The proposed model consists of eleven PDEs; however, the use of the particularphase evolving variables may reduce the model to have only six PDEs. The mainadvantage of the model is that the Abgrall's UPV criterion on mixture velocity andpressure is satisfied without affecting either its hyperbolicity or its conservations ofthe two individual masses, momentum or total energy. An Lax-Friedrichs scheme isbuilt for a particular case of the proposed model. When the two fluids in the fluid mixtureare both of the linear Mie-Gruneisen type, the scheme satisfies the Abgrall's UPVcriterion on mixture velocity and pressure. Numerical experiments with polytropic,barotropic, stiffened and van der Waals fluids show that the scheme is efficient andable to treat fluids characterized with quite different thermodynamics.